2009
DOI: 10.1093/rheumatology/kep422
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to anti-TNF therapy in ankylosing spondylitis: results from the British Society for Rheumatology Biologics Register

Abstract: Objective. Few data exist on the use of anti-TNF drugs for AS during routine clinical use in the UK. This report describes an improvement in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) after 6 months of therapy in 261 patients enrolled in a national prospective observational register.Methods. The British Society for Rheumatology Biologics Register (BSRBR) recruited patients starting anti-TNF therapy for AS between 2002 and 2006. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
86
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 19 publications
13
86
0
1
Order By: Relevance
“…A systematic literature review showed that the use of MTX prolongs TNFi 23,24 . Interestingly, major response rates within the first year in our present cohort were high and comparable to those in previous studies 5,15,25,26 . To our knowledge, we are the first to report that clinical variables quantifiable early in the treatment course, such as ASDAS-CRP inactive disease state and DAS28-remission state, could predict a 2-to 3.5-fold higher chance of 10-year drug survival in everyday clinical practice.…”
Section: Rheumatologysupporting
confidence: 91%
“…A systematic literature review showed that the use of MTX prolongs TNFi 23,24 . Interestingly, major response rates within the first year in our present cohort were high and comparable to those in previous studies 5,15,25,26 . To our knowledge, we are the first to report that clinical variables quantifiable early in the treatment course, such as ASDAS-CRP inactive disease state and DAS28-remission state, could predict a 2-to 3.5-fold higher chance of 10-year drug survival in everyday clinical practice.…”
Section: Rheumatologysupporting
confidence: 91%
“…However, we could not confirm this supposition because we did not address the reasons for corticosteroid use in our study. The frequency of corticosteroid use among patients with AS has been found to be lower in other studies, ranging from 15 to 30% at the start anti-TNF therapy [5,6]. Thus, our results should raise awareness of the potential for the irrational prescribing and use of these drugs given the risks associated with their chronic use.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, the Danish Registry found a non-significant association with gender [15]. Fibromyalgia affects 15% of AS patients in a male:female ratio of 1:3, and its symptoms of morning stiffness, fatigue and pain can lead to a confounding effect in the disease activity response, whereas the variables of anti-TNF drug and disease duration did not reach statistical significance [6,15].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Data from the British Society of Rheumatology Biologics Register has shown raised inflammatory markers at the start of therapy predicted a greater improvement in disease activity, (Lord et al, 2010). Predictors of improvement in function, measured using the BASFI, have shown a strong association with gender (significantly greater improvement in women) and concurrent DMARDs therapy (Lord et al, 2010). Finally, prevention of damage is another important outcome of therapy.…”
Section: Gene Expression Changes After Anti-tnfα Therapymentioning
confidence: 99%